Positive psychological assessment : a handbook of models and measures - Gallagher, Matthew W.; Lopez, Shane J. (American Psychological Association, 2019)
"This book is a primer for practitioners and researchers striving to incorporate the assessment of human strengths, resources, and fulfillment into their work. Contributors examine the scientific underpinnings and practical applications of measures of hope, optimism, self-efficacy, problem-solving, locus of control, creativity, wisdom, courage, positive emotion, self-esteem, love, emotional intelligence, empathy, attachment, forgiveness, humor, gratitude, faith, morality, coping, well-being, and quality of life. Vocational and multicultural applications of positive psychological assessment are also discussed, as is the measurement of contextual variables that may facilitate the development or enhancement of human strengths. This second edition includes a fully-updated research base, and extensive case studies that offer concrete examples of how clinical readers can use these tools in their practice."--